2021
DOI: 10.1097/ncc.0000000000001034
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Adaptation Process in Chinese Parent Caregivers of Pediatric Leukemia Patients

Abstract: BackgroundPsychological stresses caused by caring for pediatric leukemia patients can affect their parent caregivers’ health. How these stressors are successfully managed determines how well these caregivers adapt to the illness situation over time. Previous studies suggest that caregivers will adapt gradually to the adverse consequences of caring for their child with a long-term illness. However, studies of the psychological adaptation process of family caregivers of children with leukemia are limited.Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…The Chinese version of the Psychological Adjustment Scale [ 46 ] was employed to measure the psychological adjustment of adolescents with chronic illnesses. This is a 20-item scale composed of four subscales: coping skills (four items), self-improvement (six items), socialization (five items), and psychological development (five items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese version of the Psychological Adjustment Scale [ 46 ] was employed to measure the psychological adjustment of adolescents with chronic illnesses. This is a 20-item scale composed of four subscales: coping skills (four items), self-improvement (six items), socialization (five items), and psychological development (five items).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate better psychological adaptation. The original study reported an acceptable internal consistency (Cronbach’s a = 0.90) and construct validity (a cumulative contribution of the four factors of 55.99%) [ 46 ]. In this study, the Cronbach’s alpha of the total scale was 0.95.…”
Section: Methodsmentioning
confidence: 99%